THE ROLE OF INFORMATION SERVICES IN IMPROVING STUDENTS' CAREER PLANNING - Lolita, Nofia; Alvionita , Elica; AR, Silvia; Alrevi, Alrevi; Akbari, Akbari (Jurnal Kopendik, 2024)
Career information services play an important role in helping students understand and plan the right career path for their future, especially for teenagers who are in the transition to adulthood. This research aims to review the role of career information services in improving students' career planning. The method used is content analysis using the Krippendorff method by reviewing 20 national and international articles published in the last 10 years. Data taken from Google Scholar and Science Direct. The results of this study indicate that career information services have an important role in helping students plan their careers effectively. With the important role of career information services, counselors, guidance, and counseling teachers, and other educational practitioners are advised to continue to develop and provide these services to students.